The relationship between mindfulness, job satisfaction, and personality with burnout in nurses in hospitals: A descriptive analytical study - Uminah Uminah; Hanny Handiyani; Kuntarti Kuntarti (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Burnout is characterized by emotional exhaustion, depersonalization, and decreased personal accomplishment, often occurring in workers with intense social interactions, such as healthcare workers. Nursing is a profession vulnerable to burnout, given the high job demands, long working hours, and significant responsibility in patient care. Burnout can cause physical, emotional, and mental exhaustion, impacting the quality of healthcare services and nurses' well-being. Purpose: To determine the relationship between mindfulness, job satisfaction, and personality factors with burnout among nurses in hospitals. Method: A descriptive-analytical method with a cross-sectional design was applied. The target population included all 1,989 nurses employed at Central Hospitals in Indonesia, from which a sample of 328 respondents was drawn. Data collection was carried out using a questionnaire. For data analysis, the chi-square test was employed in the bivariate analysis, while multiple logistic regression was used for the multivariate analysis. The variable most strongly associated with the outcome was job satisfaction (OR = 17.874), whereas mindfulness showed the weakest association (OR = 4.932). Results: The logistic regression analysis revealed a significant relationship between mindfulness, job satisfaction, and personality factors with work-related fatigue (burnout) among hospital nurses, indicated by a p-value of 0.001. Conclusion: There is a relationship between mindfulness, job satisfaction, and personality factors with work fatigue (burnout) among hospital nurses.